PHOTO ELICITATION: POTRAYING THE EXPERIENCE OF TOURIST HOLIDAYING IN BALI - Yayu Indrawati (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2022)
As a social phenomenon, tourism is an activity that takes place in different cultural environment. This paper aims to explore tourism experience through the use of photo elicitation as a media for collecting data. The in-depth interviewed conducted using research participants own generated photographs that include aspects such as cultural, social and geographical. and the data emerged from tourist narratives as well as the images. Pictures captured by participants served as the baselined of interview process. Collaborative approach in which research participants portray the pictures and gives meaning to the experiences. The data analyse using qualitative approach and three themes resulted from the analysis; “portraying the sceneries”, “portraying the relationality”, “portraying the hazardous”. The initial two imply into the positive experiences, while the third theme indicates negative one. The findings in this research illustrated how the experience was highly influenced by the physical environment, natural setting of destinations as well as human interactions.